Ultrasound evolution of parenchymal changes in the thyroid gland with autoimmune thyroiditis in children prior to the development of papillary thyroid carcinoma – a follow-up study - Januś, Dominika; Kujdowicz, Monika; Wójcik, Małgorzata; Taczanowska-Niemczuk, Anna; Kiszka-Wiłkojć, Aleksandra; Górecki, Wojciech; Starzyk, Jerzy B. (Frontiers in Endocrinology, 2023)
Background Follicular cell-derived thyroid carcinoma represents the vast majority of paediatric thyroid cancers (TCs). Papillary thyroid carcinoma (PTC) accounts for over 90% of all childhood TC cases, and its incidence in paediatric patients is increasing. The objective of this follow-up study was to present the outcome of ultrasound (US) and laboratory monitoring of paediatric patients with autoimmune thyroiditis (AIT) prior to the development of PTC. Patients and methods This prospective study included 180 children and adolescents (132 females; 73.3%) with a suspicion of thyroid disorder referred to the Outpatient Endocrine Department. The patients were divided into four groups: 1) 28 patients with a mean age of 10.7 [standard deviation (SD), 3.1] y, in whom PTC was detected during the active surveillance of AIT [AIT(+), PTC(+) follow up (F)]; 2) 18 patients with a mean age of 12.8 (SD, 3.4) y, in whom PTC and AIT were detected upon admission (A) [AIT(+), PTC(+) A]; 3) 45 patients with a mean age of 13.0 (SD, 3.4) y, in whom PTC was detected upon admission and AIT was excluded [AIT(-), PTC(+) A]; and 4) an age- and sex-matched control group of 89 patients with AIT and with a mean age of 9.4 (SD, 3.0) y. The analysis included clinical, US, and laboratory assessment results of children on admission (groups 1–4) and during follow-up (groups 1 and 4) in the Paediatric Endocrine Outpatient Department. Results Upon admission of those in group 1, the US evaluation revealed a hypoechogenic thyroid gland in 12 and an irregular normoechogenic gland in 16 patients. US monitoring revealed an increase in thyroid echogenicity and an increased irregularity of the thyroid structure during the follow-up period of all of the patients from group 1. Such changes were not noticed in group 4. PTC was diagnosed at the mean time of 3.6 y (3 mo–9 y) since AIT confirmation in group 1. The mean maximum PTC diameter as per the US was significantly smaller in group 1 than in groups 2 and 3 [13.2 (10.8) mm vs. 22.2 (12.8) and 22.05 (15.4) mm]. Fewer patients in group 1 were referred to 131I than in groups 2 and 3 (71.4% vs. 94.4 and 93.3%). Interestingly, significant differences were observed in the thyroglobulin antibody (TgAb)/thyroid peroxidase antibody (TPOAb) ratio between groups 2 and 3, as opposed to group 4, at the beginning of observation [15.3 (27.6) and 3.5 (8.8] vs. 0.77 (1.9)]. In group 1, after the follow-up, an increase in the TgAb/TPOAb ratio was observed [1.2 (9.8) to 5.2 (13.5)]. There were no significant differences between groups 1–3 in labeling index Ki67, lymph nodes metastasis, extrathyroidal extension, and angioinvasion. There were no associations between thyroid-stimulating hormone, TgAb, and the extent of the disease. Conclusion The use of thyroid US focused on the search for developing tumours in the routine follow-up of patients with AIT may not only help in the early detection of thyroid malignancies that are not clinically apparent but may also influence the invasiveness of oncological therapy and reduce the future side effects of 131I therapy. We propose that the repeat evaluation of TPOAb and TgAb warrants further exploration as a strategy to determine TC susceptibility in paediatric patients with AIT in larger multicentre studies.